EFFECT OF AUTHENTIC LEADERSHIP STYLE ON EMPLOYEE ENGAGEMENT IN PUBLIC SECONDARY SCHOOLS, MURANG’A COUNTY, KENYA - Maundu, Monah N/A (Advances in Social Sciences Research Journal, 2018)
ABSTRACT This study sought to examine the effect of employee authentic leadership style on employee engagement in public secondary schools of Murang’a County in Kenya. A survey research design was employed. The target population was 3,860 teachers. Systematic random sampling followed by use of random numbers were applied to sample 368 respondents in 306 Public Secondary Schools. Data analysis was carried out using descriptive statistical methods that provide measures of central tendency like the mean, standard deviation and percentages to describe the characteristics of the variables of interest in the study. The inferential statistical tools applied in this research were correlation analysis and linear regression. Statistical Package for the Social Sciences software (SPSS) version 23 was used to assist in data analysis. The result showed that authentic leadership had a positive significant effect on employee engagement and its dimensions. Based on the findings of this study, it was established that using authentic leadership style could enhance employee engagement. This study contributes to the general understanding of leadership behaviors that are significant in encouraging employee engagement to both practicing and aspiring school leaders and teachers, and professional educator preparation programs. Key Words: Authentic Leadership, Employee Engagement, Teachers, Principals, Secondary Schools